Farm holdings and the owner’s residence location in the aspect of direct payments from the EU: A case study in nine regions in Poland - Kocur-Bera, Katarzyna (Acta geographica Slovenica, 2020)
Instruments promoting rural development have been implemented by many countries. Areabased payments for farmers allocated under the Common Agricultural Policy constitute one of such instruments in the European Union. The support system for rural areas, including the size of the declared reference parcels, is monitored as part of the cross-compliance mechanism. Parcels with unfavorable landuse patterns are more difficult to farm. According to estimates, more than 30% of agricultural farms in Poland fall into this category. This study proposes a universal algorithm for controlling the information submitted by farmers in payment applications. More than 76,000 applications were analyzed, and farms with the defective spatial structure of land were randomly selected. The results show that most errors occur in the case of land parcels situated the farthest from a farm holding (declared in the application), but the analysis revealed no strong correlation in this respect.